El cine como embajador de la diversidad cultural europea. Análisis de los largometrajes ganadores del LUX Prize - Dra. María Jesús DÍAZ-GONZÁLEZ,Dra. Almudena GONZÁLEZ DEL VALLE-BRENA (Fonseca, Journal of Communication, 2023)
The European Parliament set up the LUX Prize in 2007. The award was aimed at fostering the distribution of European films, which help to encourage European identity through film. Entries are limited to films demonstrating European values and European diversity of traditions. The films should also enlighten the integration process